B2O3 and CaO in the magnesium oxide from seawater - Martinac, Vanja (Materiali in tehnologije, 2006)
We have examined the effect of distilled water with a pH of 12.50 during the rinsing of a precipitate of magnesium hydroxide, obtained from seawater by sub-stoichiometric precipitation with 80% of the stoichiometric quantity of dolomite lime as the precipitation reagent. However, with this precipitation method the content of Bsub{2}Osub{3} in the product increases, i.e., magnesium oxide obtained from seawater. The purpose of this study was not onlyto reduce the Bsub{2}Osub{3} quantity as much as possible, but also to determine the minimum number of rinses needed to obtain calcined magnesium oxide with a satisfactory quality. Specifically, boron causes significant disturbances in the electrolysis of magnesium chloride used to obtain metal magnesium if magnesium chloride obtained from seawater is used as the cell charge, and it also adversely affects the quality of the refractory material produced from the sintered magnesium oxide obtained from seawater. The results indicate that if this method of rinsing the magnesium hydroxide precipitate is used, the Bsub{2}Osub{3} content in the MgO samples (80% precipitation) is 0.069 mass %, which is 66% less than the Bsub{2}Osub{3} content in samples prepared without rinsing the magnesium hydroxide with alkalized distilled water (Bsub{2}Osub{3}=0.200 mass %). We found that it is sufficient to carry out the rinsing by decantation three times, as further rinsing does not cause a further reduction in the amount of Bsub{2}Osub{3} in the sample. This rinsing method does not change the CaO content in calcined magnesium oxide, which indicates that further rinsing should be done with non-alkalized distilled water.
Keywords: morska voda; magnezijev hidroksid; izpiranje; usedanje; borov oksid; magnezijev oksid